Efektivitas Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Hasil Belajar Kognitif dan Social Skill Siswa SMA - Nurbaiti, Yulita; Mosik, Mosik (UPEJ Unnes Physics Education Journal, 2020)
This study applies cooperative learning type think pair share as a substitute for conventional models with lecture methods that are often used by teachers so that they do not actively involve students which results in students being sleepy and not interested in participating in learning physics. Research objectives to determine the effectiveness of the cooperative learning model type think pair share on cognitive learning outcomes and abilities social skills. This study uses a quasy experiment method with a non-equivalent control group design and purposive sampling technique for sampling. This research data collection uses test, observation, and questionnaire methods. In the experimental class the think pair share learning model was applied and the control class applied the conventional learning model. The results of the analysis of research data, obtained n-gain cognitive learning outcomes of the experimental class and the control class of 0.605 and 0.518 with the medium category. Based on the analysis of social skill questionnaire data, the n-gain of the social skills of the experimental class and control class was 0.669 and 0.541 with the medium category. The results of descriptive analysis of the wide observation of social skills in general obtained an average social skills of students in the experimental class by 84,86% with very good criteria and control class by 69,67% with good criteria. It was concluded that the cooperative learning model of think pair share type was effective enough to improve cognitive learning outcomes and social skills ability of class X high school students on business and energy materials.